Photonectes banshee, a new species of the subgenus Photonectes (Stomiiformes: Stomiidae: Melanostomiinae) from Taiwan - Koeda, Keita; Ho, Hsuan-Chign (Zootaxa, 2019)
A new scaleless dragonfish, Photonectes (Photonectes) banshee sp. nov., (Stomiiformes: Stomiidae: Melanostomiinae) is described from three specimens collected from off southwestern Taiwan. The new species can be distinguished from its congeners in the subgenus in having unique counts of photophores: IP, ventral series anterior to pectoral-fin base (6 vs. 7–13), VAV, ventral series from just behind ventral-fin base to just behind anal-fin origin (10 vs. 11–16) and VAL, lateral series from just behind ventral-fin base to just behind anal-fin origin (9 vs. 11–15) and the following combination of characters: relatively more dorsal- and anal-fin rays, lacking white luminous tissue on dorsoposterior opercle, and the presence of blue luminous tissue on mid-ventral.